2000
DOI: 10.1081/ceh-100100084
|View full text |Cite
|
Sign up to set email alerts
|

SALT INTAKE AND SENSITIVITY OF INTESTINAL AND RENAL NA+-K+ATPase TO INHIBITION BY DOPAMINE IN SPONTANEOUS HYPERTENSIVE AND WISTAR-KYOTO RATS

Abstract: The present study evaluated the activity of jejunal Na+-K+-ATPase and its sensitivity to inhibition by dopamine in spontaneous hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats during low (LS), normal (NS) and high (HS) salt intake. Basal jejunal Na+-K+-ATPase activity in SHR on LS intake was higher than in WKY rats. Jejunal Na+-K+-ATPase activity in WKY rats, but not in SHR, on LS intake was significantly reduced (20% decrease) by dopamine (1 microM) and SKF 38393 (10 nM), but not quinerolane (10 nM), this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…33 On the other hand, the mRNA corresponding to LAT2 examined by Northern blot analysis was strongly expressed in the small intestine. 34,35 In agreement with the view that LAT2 might play a role in L-DOPA transport is the recent observation that in opossum kidney (OK) renal tubular cells, L-DOPA uses at least 2 major transporters, systems LAT2 and b 0,ϩ . 17 The transport of L-DOPA by LAT2 corresponds to an Na ϩ -independent transporter with a broad specificity for small and large, neutral amino acids that is stimulated by acid pH and inhibited by 2-aminobicyclo(2,2,1)heptane-2-carboxylic acid.…”
Section: Discussionsupporting
confidence: 48%
“…33 On the other hand, the mRNA corresponding to LAT2 examined by Northern blot analysis was strongly expressed in the small intestine. 34,35 In agreement with the view that LAT2 might play a role in L-DOPA transport is the recent observation that in opossum kidney (OK) renal tubular cells, L-DOPA uses at least 2 major transporters, systems LAT2 and b 0,ϩ . 17 The transport of L-DOPA by LAT2 corresponds to an Na ϩ -independent transporter with a broad specificity for small and large, neutral amino acids that is stimulated by acid pH and inhibited by 2-aminobicyclo(2,2,1)heptane-2-carboxylic acid.…”
Section: Discussionsupporting
confidence: 48%
“…One possible explanation for the increase in urinary Na + and K + in the sik1 −/− mice without evidence of severe sodium depletion, as indicated by normal plasma Na + and K + levels, is that of a possible intestinal absorptive compensatory mechanism to keep electrolyte homeostasis. [32][33][34][35] Although we cannot exclude the possibility that renal function is affected in the sik1 −/− mice during the first days/weeks of HS intake, it is unlikely that the loss of renal SIK1 is responsible for the mild hypertension given that increased urinary Na + excretion, and not the opposite, is observed in these mice. Aldosterone levels did not differ in the sik1 −/− mice, therefore it is plausible to think that in the adrenal glands the other SIK isoforms could display compensatory mechanisms to maintain transducer of regulated cAMP response element-binding phosphorylation levels and indeed in vitro studies in adrenocortical cells showed that SIK2 and SIK3 also phosphorylate this cofactor.…”
Section: Discussionmentioning
confidence: 98%
“…The sodium balance in our studies was calculated without taking into account fecal sodium excretion. SHR have been reported to have increased intestinal sodium transport, 27,28 although fecal sodium balance was not different between WKY and SHR. 29 The decrease in positive sodium balance in AS-ODN-treated SHR was associated initially with lesser weight gain.…”
Section: Discussionmentioning
confidence: 99%